Paternalistic Leadership in Four East Asian Societies: Generalizability and Cultural Differences of the Triad Model. (January 2014) - Cheng, Bor-Shiuan; Boer, Diana; Chou, Li-Fang; Huang, Min-Ping; Yoneyama, Shigemi; Shim, Duksup; Sun, Jian-Min; Lin, Tzu-Ting; Chou, Wan-Ju; Tsai, Chou-Yu
Paternalistic leadership has been claimed to be one dominant leadership style in Asia. However, research failed to assess its comparability and applicability across East Asian contexts. The triad model of paternalistic leadership entails elements of authoritarian, benevolent, and moral character leadership. This article investigates the triad model of paternalistic leadership in mainland China, Japan, South Korea, and Taiwan. Paternalistic leadership occurs in an equivalent three-factorial structure indicating the applicability of the triad model, whereas some of the item intercepts vary between the four East Asian employee samples. These findings indicate generalizability of the meaning attributed to paternalistic leadership via three components, whereas the different measurement intercepts epitomize culture-specific scales across the four Asian contexts. The assessment of weak and strong measurement invariance is essential for an emerging cross-cultural research on paternalistic leadership by establishing evidence for the applicability and generalizability (including their boundaries) across cultural contexts.